Hubungan Pengetahuan Guru Dan Pengelola Kantin Tentang Gizi BTP (Bahan Tambahan Pangan) Terhadap Penggunaan BTP Beresiko Pada Makanan Anak SD Di Surakarta - Siti Handayani; Hartono Hartono (Poltekkes Kemenkes Surakarta, 2016)
Abstract: Knowledge, BTP, Metanyl Yellow, Rodhamin B, Borax, Formalin. The purpose of this study was to determine the relationship between knowledge Nutrition (BTP) Teachers and business school canteens with the use of food additives in food risk children in elementary schools in Surakarta. This type of research is descriptive analytic survey method. The population in this study is Professor and catering manager/ cafeteria in five elementary schools in Surakarta totaling 50 respondents, totaling 34 kinds of food samples. The sampling technique used in this study is a cluster random sampling. The statistical test used is descriptive statistics. The level of knowledge of teachers and canteen manager is; 84% good, and 16% adequate. There is no BTP (methanyl yellow, rodhamin B, borax and formaldehyde) in food in the school canteen, and there is a correlation level of knowledge with the use of BTP.